2019
DOI: 10.1080/23802359.2019.1598298
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding adjudicate two different morphs of Bascanichthys deraniyagalai (Anguilliformes: Ophichthidae): re-description and first record from Chilika lagoon, India

Abstract: Morphological characters and distribution pattern of the snake eel, Bascanichthys deraniyagalai is debatable during the past half-century. Thus, the species is re-described herewith by morphometry, vertebrae, and molecular data. In recent Chilika expedition in India, we have collected 10 specimens and observed a vertebral count dimorphism. The present study distinctly detected two vertebral groups of B. deraniyagalai: first group with 5 predorsal vertebrae, 81-83 preanal vertebrae, 190-196 total vertebrae in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the type locality, several species of Muraenidae, Ophichthidae, Apogonidae, Syganidae, etc., were also collected at the same time. Data sources: 1, this study; 2, Mohapatra et al (2019);3, Storey (1939);4, McCosker (1977);5, McCosker (1986);6, Kner & Steindachner (1867);7, Herre (1932);8, Seale (1917);9, weber (1913).…”
Section: Bascanichthys Jordan and Davis 1891mentioning
confidence: 99%
“…In the type locality, several species of Muraenidae, Ophichthidae, Apogonidae, Syganidae, etc., were also collected at the same time. Data sources: 1, this study; 2, Mohapatra et al (2019);3, Storey (1939);4, McCosker (1977);5, McCosker (1986);6, Kner & Steindachner (1867);7, Herre (1932);8, Seale (1917);9, weber (1913).…”
Section: Bascanichthys Jordan and Davis 1891mentioning
confidence: 99%
“…Eels (order Anguilliformes) are one of the abundant and important apex predators in different aquatic ecosystems; however, almost nothing is known about these processes in this large group of fishes. Only a few related cases have been reported, for instance, on a snake eel (Ophichthidae) with two distinct groups of vertebrae numbers but within the same genetic lineage (Mohapatra et al, 2019), while natural hybridization has been exclusively found in freshwater eels (Anguilla, Anguillidae; Albert et al, 2006;Avise et al, 1990;Barth et al, 2020).…”
Section: Introductionmentioning
confidence: 99%